2005
DOI: 10.1007/s11213-005-9467-1
|View full text |Cite
|
Sign up to set email alerts
|

When will a Computer Write the Auditor's Report?

Abstract: Most corporations are required by law to produce annual reports on their financial positions. These financial reports are accompanied by an auditor's report, which is an independent auditor's opinion on the fairness of the financial statements. To formulate their reports, auditors use a "personal-judgement" approach that heavily depends on their experience and expertise. This approach may be (1) ineffective and may lead to (2) different decisions, (3) personal bias, and (4) misleading judgements. These four dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similar definitions for auditing information systems are used in IT industry standards. For instance, the widely used standard "Systems and Software Engineering -Software Life Cycle Processes" states that an audit in the context of "Systems and Software Engineering" refers to an unbiased evaluation of software products and processes carried out by an authorized person in order to determine compliance with the requirements (ISO/IEC 12207:2008, 2008. Consequently, the focus of an IS audit is on the parts of the information systems that the organization uses.…”
Section: "Jurnal Inovasi Akuntansi (Jia)"mentioning
confidence: 99%
“…Similar definitions for auditing information systems are used in IT industry standards. For instance, the widely used standard "Systems and Software Engineering -Software Life Cycle Processes" states that an audit in the context of "Systems and Software Engineering" refers to an unbiased evaluation of software products and processes carried out by an authorized person in order to determine compliance with the requirements (ISO/IEC 12207:2008, 2008. Consequently, the focus of an IS audit is on the parts of the information systems that the organization uses.…”
Section: "Jurnal Inovasi Akuntansi (Jia)"mentioning
confidence: 99%
“…Conditions must be presented by the IA to apply CA technology in ERP system, (Wahdan et al, 2005b) indicated knowledge based systems in auditing would be helpful in training auditors, standardizing the procedures and report, and filling part of the lack observed in expertise and experience and in the application of auditing standards, so there are several needs for improving IA performance:…”
Section: -5 Iiamentioning
confidence: 99%
“…ARICOFR is directed in particular to the auditing practice in Egypt. This nation may have only a limited number of qualified auditors who are sufficient in evaluating the internal controls, in particular in E-Commerce environment (Wahdan, et al, 2005;Wahdan, & Van den Herik, 2012).…”
Section: Introductionmentioning
confidence: 99%